Optimalisasi Produksi Kue Kering Yayasan Amal Mulia Indonesia Menggunakan Program Linier Metode Substitusi - Latifah, Siti; Akbar, Gustomi; Nur Ribkhah, Sifa (Jurnal Etnik: Ekonomi-Teknik, 2023)
One of the basic things that can be done to anticipate the negative impact of rising prices of production materials is to re-analyze the prices of production materials with the selling prices of production using a linear program. In this study, the analysis technique used was linear programming using the substitution method to obtain profit predictions from selling Cookies. The purpose of this study is to determine the optimization of pastries production to generate maximum profit. The case study was conducted in the Pastry Business at the Mulia Amal Foundation, South Jakarta, Indonesia. The results of the research on optimizing the production of the KUKERAMI pastry business Yayasan Amal Mulia Indonesia produces with optimal results, the profit earned on last year's sales using the linear program substitution method achieved a profit of IDR 6,900,000 by selling chocolate cookies and snow white cookies, 70 jars each and 60 jars.